2003
DOI: 10.1113/jphysiol.2003.044784
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal cell communication within local networks in layer 2/3 of rat neocortex

Abstract: The extent to which neocortical pyramidal cells function as a local network is determined by the strength and probability of their connections. By mapping connections between pyramidal cells we show here that in a local network of about 600 pyramidal cells located within a cylindrical volume of 200 microm x 200 microm of neocortical layer 2/3, an individual pyramidal cell receives synaptic inputs from about 30 other pyramidal neurons, with the majority of EPSP amplitudes in the 0.2-1.0 mV range. The probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
488
5
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 546 publications
(561 citation statements)
references
References 46 publications
66
488
5
2
Order By: Relevance
“…In our models, each neuron had a Gaussian dendritic field of ρ d = 75 μm (corresponding to an approximate width of 4ρ = 300 μm; [59]); and axonal field of ρ a,e = 290 μm for excitatory neurons (width 1100 μm; [59][60][61]) and ρ a,i = 100 μm for inhibitory neurons (width 400 μm; [62]). Table 2.…”
Section: Large-scale Model Of Local Connectivity In Mouse V1mentioning
confidence: 99%
“…In our models, each neuron had a Gaussian dendritic field of ρ d = 75 μm (corresponding to an approximate width of 4ρ = 300 μm; [59]); and axonal field of ρ a,e = 290 μm for excitatory neurons (width 1100 μm; [59][60][61]) and ρ a,i = 100 μm for inhibitory neurons (width 400 μm; [62]). Table 2.…”
Section: Large-scale Model Of Local Connectivity In Mouse V1mentioning
confidence: 99%
“…The balance of excitatory and inhibitory synapses is crucial for that propagation [45]. Indeed, in vivo experiments showed that computation proceeds by direct pyramidal-pyramidal cell communication in the neocortex [46] and assemblies may transiently form [47]. Firing rate modulations are transmitted linearly through many layers in neocortex [48].…”
Section: Discussionmentioning
confidence: 99%
“…The connectivity probability for excitatory and inhibitory neurons was varied independently and is defined as the percentage of neurons that a neuron connects to within its local range. In neocortical tissue, local functional connectivity between neurons decays with distance; however, only a few empirical reports have assessed this quantitatively [62,63]. Given the small radius of connectivity, this was implemented as an exponential decay.…”
Section: Critical Oscillations Model (Cros)mentioning
confidence: 99%